CRISPR/Cas Genome Editing—Can It Become a Game Changer in Future Fisheries Sector? - Roy, Suvra; Kumar, Vikash; Behera, Bijay Kumar; Parhi, Janmejay; Mohapatra, Sipra; Chakraborty, Tapas; Das, Basanta Kumar (Frontiers in Marine Science, 2022)
Fisheries and aquaculture is the fastest growing food producing sector and rapidly becoming an important element for the global food security since it is the primary source of seafood and high animal protein in human diet. Genome editing offers new possibilities such as CRISPR/Cas9 technology has the potential to accelerate the sustainable genetic improvement in fisheries and aquaculture. CRISPR/Cas9 system has four key components namely target DNA, Cas9, PAM (protospacer adjacent motif) sequence and the guide RNA or single guide RNA (gRNA or sgRNA). CRISPR/Cas is cheaper, easier and precise than the other genome editing technologies and can be used as a new breeding technology in fisheries and aquaculture to solve the far-reaching challenges. The attributes like high fecundity, external fertilization, short generation-interval, established method of breeding and larval rearing of most aquaculture species have advantages for CRISPR/Cas9 genome editing applications. CRISPR/Cas9 has recently been applied to traits valued in some aquaculture species (almost >20 species) targeting the main traits of traditional genetic improvement initiatives like growth, disease resistance, reproduction, sterility and pigmentation. Genome editing can fast forward the breeding process with precision where changes occurs at the targeted genes, rather in selective breeding where changes is random and many generations is needed to establish a new breed. Moreover, CRISPR/Cas genome editing rapidly introduces favorable changes by disrupting genes with targeted minor changes, in contrast to transgenesis which introduce foreign genes into the host genome and thereby alleviating major public concerns on safety. Though CRISPR/Cas technology has tremendous potential, however several technical challenges, regulatory and public issues concerning the applications in fisheries and aquaculture breeding sector. Nonetheless, the exciting point in the CRISPR/Cas9 genome editing that two CRISPR-edited fish namely red sea bream and tiger puffer developed by the Kyoto-based startup got approval and are now on the market for sale and another fish FLT-01 Nile tilapia developed by the AquaBounty is not classified under GMO regulatory. However there is still a way to go before it revolutionize and becomes viable in commercial aquaculture as new breeding technology for aquaculture important traits and species.